The implementation of teaching reading using the phonics approach in year 1 ESL classroom / Zahirah Zulkifli - Zulkifli, Zahirah (2014)
The use of phonics approach as one of the teaching strategies in teaching reading is not new in the world of literacy. Malaysia has introduced the phonics approach in teaching reading based on the ‘Back to Basics’ principle outlined in the new Standard Curriculum for Primary School (KSSR) whereby it stresses on the importance of having a strong foundation in the English Language. It is believed that the phonics approach introduced can be one of the effective teaching strategies in order to help young students begin to read. This study looks at the use of phonics approach in Year 1 English language classrooms particularly in reading lessons. Specifically, this study focused on a) the teachers’ knowledge and understanding of phonics, b) teachers’ teaching practices when using phonics approach and c) the challenges encountered by teachers when using phonics approach to teach reading. This study employed a qualitative approach whereby it used the classroom observations, interviews and document analysis as the main instruments. This study involved only three English language teachers who are currently teaching Year 1 in the district of Kuala Selangor, Selangor. The classroom observations were conducted twice for each participant followed by an interview. Then, the analysis of participants’ lesson plans of two reading lessons, the Curriculum Standard Document for English Language Year 1 and Teachers’ Guidebook for English Language Year 1 was made to further strengthen the data collected. The findings illustrated that the teachers possessed little knowledge and understanding on phonics and their knowledge was limited to knowledge of sounds and letters. Furthermore, the results indicated that teachers are most familiar with direct phonics instructions when teaching reading using phonics approach as they always introduced the phonemes followed by the associated words. Interestingly, findings also found that a teacher used embedded phonics instructions by using authentic texts without realising that those texts are beneficial to be used together with phonics approach. The findings also revealed two major concern when using the phonics approach which are teachers’ conventional views on phonics as well as lack of support in terms of teaching materials and trainings. Thus, the findings propose that teachers must be provided with sufficient training and support of teaching materials and authentic texts. It is also recommended that teachers are provided with continuous development programme on current teaching strategies using phonics approach. Finally, this study suggests that teachers take the initiative to vary their teaching practices by using different phonics instructions and constantly improving themselves by taking part in a learning community.